Prevalência da respiração bucal e má oclusão em escolares e impacto na qualidade de vida relacionada à saúde bucal: estudo clínico epidemiológico da Cidade de Diamantina-MG - Soraia Pimenta de Araujo Guimar?es (2013)
Abstract - Introduction: The aim of this cross-sectional population study was to evaluate the prevalence of mouth breathing and malocclusion in schoolchildren 8-10 years old in the city of Diamantina/MG and impact on quality of life related to oral health. Methods: The sample consisted of 390 children randomly selected from a population of 1462 students. Data collection was obtained through clinical examinations to assess breathing, changes facial and dental arches, and application of two questionnaires. The "Child Perceptions Questionnaire" - CPQ (8-10) was used to assess the quality of life related to oral health and the questionnaire Abep, to assess socioeconomic conditions. The examination of water retention associated with haze metallic mirror Glatzel were used for clinical assessment of mouth breathing. We evaluated the nasal patency by measuring peak nasal inspiratory flow (PNIF) and used photogrammetry to assess the posture of the head and neck. Indexes WHO DMFT / dmft for evaluation of oral health and dental aesthetics (DAI) for evaluation of malocclusion were used. Data collection was obtained in 2013, within a period of six months. Results: The prevalence of mouth breathing was 11.8% and malocclusion was 78.7%. Signs and symptoms studied, such as snoring, nasal obstruction daily, difficulty breathing night, adenoid facies and lack of lip seal were highly associated with mouth breathing. By Mann-Whitney can prove that mouth breathing is strongly associated impact on oral health related to the quality of life. In the final model of Hierarchical Poisson regression showed that the impact on oral health related to the quality of life was significantly associated with mouth breathing [OR = 1.37 (95% CI: 1.11 to 1.71) p <0.004], controlled by caries [OR = 1.64 (95% CI: 1.36 to 1.97) p <0.001] and socioeconomic status [OR = 1.32 (95% CI: 1.10 to 1, 57) p <0.002]. With regard will malocclusion, the final model of Hierarchical Poisson regression showed that the impact on oral health related to the quality of life showed significant association with malocclusion (anterior crossbite [OR = 1.28 (95% CI: 1.17 to 1.39) p <0.001]) controlled by caries [OR = 1.25 (95% CI: 1.03 to 1.51) p = 0.022]. Conclusion: The prevalence of mouth breathing was low (11.8%) and malocclusion was considered high (78.7%). Changes related orofacial will mouth breathing were strongly associated. The negative effect of mouth breathing and malocclusion on oral health related to the quality of life of schoolchildren 8-10 years of Diamantina/MG was significant.